TINGKAT KETERAMPILAN PERMAINAN BOLA KASTI SEKOLAH DASAR NEGERI COT PREH KUTA BARO ACEH BESAR - Husaini, Husaini; Kurniawan, Erizal; Syahrianursaifi, Syahrianursaifi; Jannah, Raudhatul (Jurnal Dedikasi Pendidikan, 2024)
The game of baseball is part of small ball which is included in the elementary school learning curriculum. The purpose of this study was to determine the level of skills of the baseball game at Cot Preh State Elementary School. This research uses descriptive quantitative with survey method. The population and research sample were Cot Preh State Elementary School students totaling 23 students with purposive sampling technique. Research collection instruments and techniques using tests and measurements of baseball skills, namely: 1) ball catching test, 2) ball hitting test, and 3) ball throwing test. Data is analyzed through percentages. The research results obtained were in the sufficient category (34.78%) with details: 1) very high category with a frequency of 2 students (8.70%), 2) high category with a frequency of 5 students (21.74%), 3) sufficient category with a frequency of 8 students (34.78%) 4) low category with a frequency of 8 students (34.78%) 5). The conclusion of the study is that the level of skill of the baseball game at Cot Preh State Elementary School is categorized as sufficient.